A Bio‐Inspired, Heavy‐Metal‐Free, Dual‐Electrolyte Liquid Battery towards Sustainable Energy Storage. Issue 15 (9th March 2016) - Ding, Yu; Yu, Guihua
Abstract: Wide‐scale exploitation of renewable energy requires low‐cost efficient energy storage devices. The use of metal‐free, inexpensive redox‐active organic materials represents a promising direction for environmental‐friendly, cost‐effective sustainable energy storage. To this end, a liquid battery is designed using hydroquinone (H2 BQ) aqueous solution as catholyte and graphite in aprotic electrolyte as anode. The working potential can reach 3.4 V, with specific capacity of 395 mA h g −1 and stable capacity retention about 99.7 % per cycle. Such high potential and capacity is achieved using only C, H and O atoms as building blocks for redox species, and the replacement of Li metal with graphite anode can circumvent potential safety issues. As H2 BQ can be extracted from biomass directly and its redox reaction mimics the bio‐electrochemical process of quinones in nature, using such a bio‐inspired organic compound in batteries enables access to greener and more sustainable energy‐storage technology. Abstract : Versatile energy‐storage devices : The use of metal‐free redox‐active organic materials is promising for the development of environmental‐friendly, cost‐effective, and sustainable energy‐storage devices. As hydroquinone can be extracted from biomass directly, using such a bio‐inspired organic compound in batteries enables access to green and sustainable energy‐storage technology.